CBMT-21. ALTERATIONS OF CYSTEINE METABOLISM IN GENETIC VARIANTS OF HIGH GRADE GLIOMAS. (5th November 2018) - Lechpammer, Mirna; Rabow, Zachary; Morningstar, Taryn; Gagner, Jean-Pierre; Shahlaie, Kiarash; Girgis, Fady; Green, Ralph; Nudler, Evgeny; Zagzag, David
Abstract: Isocitrate dehydrogenase (IDH) mutation have been reported to impose in gliomas a shortage of NADPH required to maintain a redox state and may rely on cysteine (Cys) availability for biosynthesis of glutathione (GSH) to ensure antioxidant levels. Cys may be replenished via extracellular intake or by de novo intracellular synthesis via transsulfuration (TS) pathway. The aim of this study was to investigate alterations of Cys metabolism in genetic variants of high-grade gliomas (HGG). Seventeen tumor samples from 15 adult patients (11 M / 4 F; average age 57 years, range 25 – 81 years), who underwent surgical resection for newly diagnosed or recurrent HGG were analyzed by HPLC. Levels of Cys, homocysteine and GSH were correlated with the genetic signature of HGG (wild-types vs. IDH1 mutation, PTEN deletion, EGFR amplification and MGMT methylation). Cys levels were significantly higher (2.1 fold increase; p=0.0038) in IDH1-mut (n=4) vs. IDH1-wt HGG (n=13), with comparable homocysteine and GSH levels. PTEN deletion and EGFR amplification did not significantly alter Cys metabolites with comparable levels of Cys, homocysteine and GSH detected in PTEN-del (n=7) and PTEN-intact (n=6) HGG, as well as in EGFR-amp (n=7) and EGFR-non amp (n=9) HGG. Significantly higher Cys levels (3.2 fold increase; p=0.0186) were also found in MGMT methylated (n=4) vs. non-methylated (n=3) HGG, with comparable levels of homocysteine and GSH. Increased Cys levels detected in IDH1-mut and MGMT methylated HGG support the hypothesis that these tumors may preferentially use the TS pathway for GSH synthesis. These findings are consistent with our report of increased TS pathway enzyme cystathionine B-synthase (CBS) in HGG, but concurrent increased intake of Cys cannot be excluded. Our results suggest utilizing Cys metabolites as potential markers and/or therapeutic targets in some genetic variants of HGG, a hypothesis that should be further explored in larger translational trials.